Therapeutic effects of momordica charantia L. Ethanolic extract on acetic acid-induced ulcerative colitis in rats - ŞEN, ALİ; KAYA, ÖZLEM TUĞÇE; ŞENKARDEŞ, İSMAİL; ÖZBEYLİ, DİLEK (My University, 2021)
© 2021 European Journal of Biology. All rights reserved.Objective: This study aims to investigate the effect of Momordica charantia L. (MoC) ethanolic extract on ulcerative colitis (UC) and was explored in vitro and in vivo. Materials and Methods: The rats were divided into control (C), saline-treated colitis (AA), MoC extract-treated colitis (AA+MoC), and sulfasalazine (SS)-treated colitis (AA+SS) groups. Colitis was induced by acetic acid. MoC extract, SS or saline were given to the related groups for 3 days. Interleukine-1β, malondialdehyde, glutathione levels, myeloperoxidase activity, bax/bcl-2 ratio, caspase-9 and caspase-3 levels were measured in colon and macroscopic and histopathologic examinations were done. Total phenolic/flavonoid content and biological activity of MoC were evaluated by in vitro analysis. Results: Compared to the control group, with acetic acid application interleukin-1β levels, myeloperoxidase activity, malondialdehyde levels, bax/bcl-2 ratio, caspase-9 and caspase-3 levels were significantly upregulated, while glutathione levels were significantly decreased in the AA group. In contrast, MoC and SS treatments reduced interleukin-1β, malondialdehyde levels, myeloperoxidase activity, bax/bcl-2 ratio, and caspase-9 and caspase-3 levels. Glutathione levels increased upon MoC or SS treatment. Increased macroscopic and microscopic scoring with AA improved with MoC or SS treatment, but the MoC or SS treated groups had higher score values than the control. Also, in vitro results showed that MoC exhibited 2,2-diphenyl-1- picrylhydrazyl and 2,2\"-azino-bis-3-ethylbenzothiazoline-6-sulfonic acid radical scavenging activity as well as significant antilipoxygenase activity. In addition, MoC extract showed a potent anti-inflammatory activity compared to standard indomethacin. Conclusion: Our biochemical, in vitro and histopathologic analysis indicate that MoC is likely to prove beneficial in UC therapy.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Histoloji-Embriyoloji; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Temel Bilimler; Medicine; Health Sciences; Fundamental Medical Sciences; Histology and Embryology; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Natural Sciences; Yaşam Bilimleri (LIFE); Moleküler Biyoloji ve Genetik; Mikrobiyoloji; HÜCRE BİYOLOJİSİ; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Life Sciences (LIFE); MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; CELL BIOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; Hücre Biyolojisi; Moleküler Biyoloji; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Cell Biology; Molecular Biology; Biochemistry, Genetics and Molecular Biology (miscellaneous); anti-lipoxygenase activity; apoptosis; Momordica charantia L.; oxidative stress; radical scavenging activity; ulcerative colitis; :Momordica charantia L.; ulcerative colitis; apoptosis; oxidative stress; radical scavenging activity; anti-lipoxygenase activity